Pengaruh Penambahan Carboxymethyl Cellulose (CMC) dan Gelatin sebagai Bahan Pengikat pada Pembuatan Tablet Kulit Manggis (Garcinia Mangostana L) - Ahmad Shobib; MF. Sri Mulyaningsih; Ery Fatarina (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Mangosteenis one of thefavorite fruits are favored by the people of Indonesia.Mangosteen is a plant that has a high economic value because in addition to consume fruit, mangosteen peel can also beused in traditional medicine, namely to treat upset stomach, diarrhea, dysentery, and wound infections.The main content of the compounds contained in the skin ofthe mangosteen is axanthone has anti microbial properties, antiinflammatory, antioxidant, and can inhibit the growth of colon cancercells. Mangosteen rind discarded, it can be developed as drug candidates. Tablets in solid dosage forms containing drug with or with out filler.Binder affects the quality ofthe physical tablet. This study usedthe CMC(Carboxymethyl celulose) and gelatin as a binderin the manufacture of tablets mangosteen skin.Research is descriptive research. The object under study is mangosteen skin tablet. This study covers the water contentand physical characteristics of skin mangosteen tablets. The result showed mangosteen skin moisture content of 67.11% and 32.89% mangosteen skin powder. And the results of the study of physical characteristics of tablets obtained the optimum results from the binder used is a tablet with the addition of CMC mangosteen peel 15 grams. Achieved average weight uniformity(CV) was4.18%. Tablet hardness was 5.93kg. Fragility tablet is 0.46%. Tablet disintegration time was 8.89minutes.